MIDWIFE CARE FOR PREGNANT BREECH MOTHERS WITH FOCUS KNEE CHEST POSITION INTERVENTION TO CHANGE PRESENTATION OF THE FETAL AT PURWODADI PUSKESMAS I - Mar'atul Azizah; Dhiyan Nany Wigati; Sri Untari (The Shine Cahaya Dunia Kebidanan, 2023)
Background; Pregnancy is an event that starts from conception then will develop until the occurrence of an aterm pregnancy and ends with the delivery process. Pregnancy means a natural event for women, a woman will experience changes in herself, both physically and psychologically, the physical changes that are often found in the third trimester, namely the stomach increases in size with gestational age, pain in the upper left abdomen is often experienced by pregnant women due to the body producing and preparing additional fluids. During pregnancy, as a result, most pregnant women experience swelling, especially at the end of pregnancy. Edema often appears on the legs, heels, and face due to the origin of the focus in the uterus. Method; The research plan that the researcher uses is a case study research plan. This type of descriptive case study research uses participatory observation method. The subjects in this study were breech pregnant women from 28 weeks to 36 weeks of gestation. Results; The results showed that the diagnosis in the case of Ny. Y age 32 years G3P2A0 gestational age 29+4 weeks with fetal presentation i.e. head. Conclusion; Pregnant women with a breech position have been resolved.